TANGUNG JAWAB DAN LANGKAH PENCEGAHAN AKULAKU DALAM MENJAMIN KEAMANAN AKUN KONSUMEN - Millatina Azizah Virdiani (2021)
The Akulaku application is an online consumer financing. Problems arise when there has been a breach of service user accounts that has caused losses to service users. Robby felt aggrieved because suddenly in his account there was a bill of Rp. 5,000,000 and Robby asked Akulaku to take responsibility but did not come up with a good enough solution. For this reason, it is necessary to research whether the responsible actions taken by Akulaku are in accordance with existing regulations. This research is a normative study using a statutory approach. The legal materials used include primary, secondary, and tertiary legal materials. The results show that Akulaku's actions to make compensation are in accordance with Article 19 of the UUPK but there are still many violations committed by Akulaku according to the ITE Law, 2016 Menkominfo Regulation, POJK No. 1 / POJK.07 / 2013 and POJK No. 13 / POJK.02 / 2018